Athletics, Academics, and the Financial Condition of U.S. Private Colleges - Jody W Lipford; Jerry K Slice (Journal of Applied Sports Management, 2022)
Abstract Many private colleges in the U.S. face financial difficulty. The role of athletics in the financial condition of U.S. colleges is subject to controversy. Supporters argue that collegiate sports draw students, improve student quality, and increase donor support. Detractors argue that athletics are costly and undermine the academic mission of the institution. In this paper, we examine metrics of athletic and academic quality to determine their effects on the financial health of a sample of U.S. private colleges. Our findings indicate that higher spending on athletics reduces an institution’s financial health and that academic quality increases an institution’s financial health.
Keywords: private colleges; college finance; college athletics; college academics